AquaFarm Ace: A Game on the Intensive Aquaculture Process of Oreochromis niloticus (International Conference on Computers in Education, 2023)
As Aquaculture accounts for 52.4% of the fishing industry in the Philippines, it boasts potential in providing a stable source of food and livelihood. AquaFarm Ace is a 2D Time-Management simulation game on the intensive aquaculture process. The player takes the role of an aquaculturist as they go through the various stages of aquaculture. The game showcases hatchery, transportation, grow-out, and brood stock stages in the aquaculture stages of Oreochromis noliticus. This study aims to contribute to the scholarly community of aquaculture and serious game design. The game was developed using the following tools: Aseprite, beepbox.co and Unity 2020.3.181f and is made available through Unity Play. The researchers selected volunteer participants to play test the game and answer pretest, post-test, and game experiences questionnaires to gather data in relation to the effectiveness of the game. The results show that AquaFarm Ace contributes to raising awareness of aquaculture and can play a key role in highlighting its increasing demand in the aquatic scene in the Philippines to alleviate the socioeconomic problems such as food and job security. To note, play testers retained information about the aquaculture process of O. niloticus after playing the game. As shown on the Game Experience survey, the testers see the game as an enjoyable experience and a potential tool to teach aquaculture.